The gendered response to farmer-herder violent conflict in Nigeria - Bloem, Jeffrey R.; Damon, Amy; Francis, David C.; Mitchell, Harrison (International Food Policy Research Institute, 2025)
From 2010-2020, Nigeria experienced a sharp rise in violence propagated by the jihadist group Boko Haram in the northeast region and escalating inter-group conflict between farmers and Fulani pastoralists in the north-central region. Boko Haram’s violent attacks led to states of emergency in both 2011 and 2013; and while that group has dominated the news, conflicts between Fulani pastoralists and settled agricultural communities are often more deadly.